EFFECTIVENESS of Turbinaria conoides AS A HAIR TONIC FOR HAIR GROWTH IN MICE (Mus musculus) - Afifah Nurazizatul Hasanah; Ginanjar Pratama; St. Nurul Fadillah (Jurnal Perikanan dan Kelautan, 2025)
Hair loss is a common condition that may reduce self-confidence. Hair tonics are product that used to maintain scalp health, strengthen hair follicles, and stimulate hair growth. However, commercially available products often contain synthetic compounds, which may cause adverse side effects. Therefore, the development of safer hair tonic formulations is needed. Turbinaria conoides, a brown seaweed rich in flavonoids, and celery (Apium graveolens) have been reported to possess bioactive properties that support hair growth. This study evaluated the effect of incorporating T. conoides and celery extracts into hair tonic formulations on hair growth. The research was conducted in three stages: extraction of raw materials, formulation of hair tonic preparations, and in vivo testing using mice as experimental animal models. Hair growth was assessed by measuring hair length periodically from day 7 to day 28 following topical application.. Among the tested formulations, P4 (10% seaweed extract and 0% celery extract) demonstrated the best performance with characteristics as follow: produced the highest hair growth of 11.28 mm and the highest increase in hair weight of 0.12 grams; pH 5,6 (in safe range); shows good physical stability; and demonstrated panelist acceptance at a score of 3 (like category) based on a hedonic test for color and aroma parameters. Hair tonic formulated with T. conoides and celery extracts shows potential as a natural and effective alternative for promoting hair growth and may reduce reliance on synthetic agents.